Building on strengths in Naujaat: the process of engaging Inuit youth in suicide prevention. Issue 2 (28th January 2019) - Anang, Polina; Naujaat Elder, Elizabeth Haqpi; Gordon, Ellen; Gottlieb, Nora; Bronson, Maria
ABSTRACT: Death by suicide and attempted suicide among Inuit youth is now considered a public health emergency of epidemic proportion, with rates among the highest worldwide. A strong sense of cultural identity and pride, as well as social capital, has been identified as being protective against suicide. The Canadian Institute for Health Research (CIHR) Guidelines for Health Research Involving Aboriginal People call for communities to be included in the conception, planning and implementation of research. The authors took first steps towards sharing the responsibility of designing a community initiative with the youth of Naujaat, Nunavut, a community located directly on the Arctic Circle. With the objectives of promoting open listening and exploration of community needs and enhancing self-determination and sustainability, we postulated a youth resiliency project that will be co-authored by the community. This paper describes the joint work process. We recount how Inuit youth take ownership of the project with the guidance of Ms. Elizabeth Haqpi, a Naujaat Elder. The article will particularly reflect on the process of balancing the different perspectives and expectations while enjoying the richness of mutual learning through keeping each other accountable.